A Comparison of the Cattail Pollen (Typha angustifolia L.) Adhesion on Different Fabrics - Vichitnark, Pimrumpa; Taechowisan, Thongchai; Sinloyma, Patchara (Naresuan University Journal: Science and Technology (NUJST), 2020)
As pollen has been produce vastly and it can be recovered from a variety of sources because of its resistance to destroy. Moreover, it can be preserved for many years without particularizing storage, pollens can be identified to a specific plant type, site, region, or country of their origin. It can adhere to various surfaces and can be attached tightly. The pollen has a unique characteristic which suitable for identification similar to a pollen print. which brings to assume or predict place or environment around the crime scene. Pollen can be used to link to victims, suspects, and objects related to the crime scene or reconstruct situations to identify the location of pollen. The reference pollen in this study is a cattail pollen ( Typha angustifolia L.) because it is a plant that can be seen all over Thailand, currently widespread throughout the world. This grass usually grows covered up tightly in areas that are overgrown and dirty place and it can produce much pollen thus conceal the murder. The objectives of this research were to compare the adhesive efficacy of the cattail pollen on different fabrics and study palynological characteristic of cattail pollen. This study could be used to consider the part of supportive document in forensic investigation and help depicting how to use the Hirox® program in analyzing the result. The population of cattail pollen grains used in this experiment was collected in the area of Phitsanulok province. Three types of fabrics including cotton, denim and polyester were dust with pollen grains and left undisturbed for four different periods of time (1 day, 3 days, 5 days and 7 days) before studying the adhesive capability and palynological characteristic of pollen. Scanning electron Microscope was used in characteristic study, while the pollen counting was performed on the light microscope with the help of the Hirox® software and the Hirox® microscope in RGB counting mode. All data were statistically analyzed by One-Way ANOVA, which analyzing the differentiation of the pollen quantity on different fabrics. The result revealed a statistically significant difference at the p < 0.05 level between groups of fabrics. The quantity of pollen grains adhering to the fabrics showed the highest value on the polyester, followed by the denim, whereas the cotton found lowest amount. Keywords: Pollen, Forensic science, Biological evidence, Microscope, Typha angustifolia L.